'Symposium on Syndicalism' by Tom Mann, 1910 (1910)
1910 1880-1914 "'Symposium on Syndicalism' by Tom Mann, 1910" [T0188.jpg], 1910 No. 5 in a series of pamphlets on syndicalism, entitled 'The Industrial Syndicalist' which was edited by Tom Mann. The other articles in this issue are "The Miners' Hope" by W. F. Hay of the South Wales Miners' Federation, "The Need for Education in the Trades Unions" by T. J. Ring, and "Working-Class Socialism" by E. J. B. Allen.